Effects of quality grade, aging period, blade tenderization, and degree of doneness on tenderness of inside round steaks - George-Evins, C.D.; Unruh, John A.; Marsden, James L.; Kastner, Curtis L. (Kansas State University. Agricultural Experiment Station and Cooperative Extension Service, 2010)
We used 162 inside rounds to determine the influence of different quality grades, postmortem aging periods, blade tenderization passes, and degree of doneness on thawing and cooking losses and Warner-Bratzler Shear force (WBS, tenderness). Select (SEL), Choice (CHO), and Certified Angus Beef™ (CAB) inside rounds were aged for 7, 14, or 21 days and not tenderized (0X) or blade tenderized one (1X) or two (2X) times. Steaks from each inside round were assigned randomly to final endpoint cooking temperatures of 150, 160, and 170°F. Percentage of thawing loss was higher (P<.05) for steaks aged 7 days than steaks aged 14 and 21 days. For CHO steaks only, cooking loss was higher (P<.05) for the 2X group compared to the 0X and 1X groups. Steaks aged 14 and 21 days had lower (P<.05) WBS than steaks aged 7 days. Cooking loss and WBS were higher (P<.05) with each increase in endpoint cooking temperature. Postmortem aging (14 or 21 days) and lower endpoint cooking temperatures were the most effective methods to improve WBS of inside round steaks.
Keywords: Beef; Tenderness; Blade tenderization; Aging; Quality grade